Pengembangan Pengelolaan Perangkat Pembelajaran Praktik Berbasis Lingkungan dalam Penunjang Pembelajaran Kimia - Eristiana, Eristiana; Warlizasusi, Jumira; Sutarto, Sutarto (JOEAI (Journal of Education and Instruction), 2023)
This study aims to develop practical learning tools based on the environment to support chemistry learning for students at MAN 2 Lahat. This research uses a 3-D model; define (defining) by analyzing the students, teachers and materials. Design (Planning) by making product designs and developing (development), namely conducting validation and particularity tests. Implementation of practicum at MAN 2 Lahat in class X MIA, X IIS and X IIK students used an environment-based practicum method with enthusiasm, enthusiasm and a sense of responsibility. The validation results of the experts reached a score of 3.87 which was categorized as very valid and the test of environment-based learning tools reached a very practical implementation percentage of 96.67%. In conclusion, the environment-based practical learning tools developed to support chemistry learning for students at MAN 2 Lahat are declared valid and feasible to be used to support learning. Keywords: Development, Management, Practical Learning Devices